Green Chemistry — Present and Future Issues - Dhiman, Vijayant (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The basis of green chemistry is frequently considered as a response to theneed to reduce the damage of the environment by man-made materials and theprocesses used to produce them. A quick view of green chemistry issues in thepast decade demonstrates many methodologies that protect human health and theenvironment in an economically beneficial manner. This article presents selectedexamples of the implementation of green chemistry principles in everyday life inindustry, the laboratory and in education. A brief history of green chemistry andfuture challenges are also mentioned.